Systematic Literature Review (SLR): Integrated Problem-Based Learning (PBL) Model for Ecotourism to Enhance Scientific Literacy and Environmental Awareness - Khaerus Syahidi; A. Wahab Jufri; Aris Doyan; Kosim Kosim; Joni Rokhmat; AA Sukarso (Jurnal Penelitian Pendidikan IPA, 2024)
The problem-based learning (PBL) model is a form of learning that emphasizes the learning process and developing problem-solving skills. The low level of environmental awareness is increasingly worrying. Ecological awareness, in this case ecotourism, is decreasing along with technological developments. For this reason, scientific literacy and environmental awareness are needed, especially in character formation. This article research conducted a systematic literature review using PRISMA approach, namely carrying out a synthesis of studies from articles on the theme of the ecotourism-integrated problem-based learning (PBL) model to increase scientific literacy and environmental awareness. The articles used in this paper are from Google Scholar, scopus and science direct with the application of proportional sampling techniques, 15 of the 72 articles that meet the inclusion criteria, the year of publication between 2020 until 2024, the languages used are Indonesian and English, the research subject is Problem-Based Learning (PBL). The research results show that PBL has positive potential in increasing scientific literacy and environmental awareness. Both the use of the PBL model directly and with integration show an increase in scientific literacy and concern for the environment